"Determinants of Household's energy consumption preference and its implication to climate changes and economic development of the Kano state of Nigeria". (2022) - Sani Bala, Ahmad; Junaid Alam, Mohammad; Shehu Shuaibu, Muhammad; Singh, Animesh; Chaturvedi, Sharad
Abstract: Energy consumption is always a matter of concern especially to developing and underdeveloped nations throughout the globe. Nigeria and its rural and urban demand for the energy resources is an issue that has similar concerns and challenges. There appears to be a great dilemma of the level of energy demand and its consumption pattern. The positive side of this appears in the form of energy demand of industrialization and production enhancement, whereas the negative side of the same appears to manifest in form of global warming, exploitation and pollution. Thus, it is important for any nation to optimize the consumption pattern for the sake of economic development under the sustainable framework. Although Nigeria is one of the major oil producers and rich in sources of energy apart from oil such as wood, coal, gas, tar sands, and hydro power etc., the optimization of consumption pattern is below par the global levels. This research paper is intended to find out the determinants of energy consumption and its impact over climate with the help of evaluation of the sample from Kano State. The study is based upon direct survey from households using questionnaire. Total sample size was 300 to understand the determinants and consumption pattern in the state. Further, data was analyzed using the required statistical tools and it was extracted that considerably many factors affect the energy consumption preference beside those tested by the one-way ANOVA. Income, education and family size are the tested factors affecting the family energy consumption preference. Beside these, household willingness, occupations, perception of the danger of modern energy to the household as well as the threat of traditional energy sources to climate change were also found to play a significant role in the energy consumption preference.